1990
DOI: 10.3102/00028312027002323
|View full text |Cite
|
Sign up to set email alerts
|

Testing a Model of Teacher Satisfaction for Blacks and Whites

Abstract: The purpose of this study was to construct and test a model of the influences affecting early-career teachers 'job satisfaction. The path model is presented and tested first with a sample of black teachers and then with a sample of white teachers. Although the model provides a plausible explanation for the relationships among the variables for both groups, differences in the structural coefficients indicate the process leading to teacher job satisfaction is different for blacks and whites. The implications of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
1
2

Year Published

1993
1993
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 25 publications
2
24
1
2
Order By: Relevance
“…However, the direction of Educational Psychology 479 this relationship is uncertain. While some researchers have claimed that organizational commitment influences job satisfaction (Culver, Wolfle, & Cross, 1990; Vandenberg & Lance, 1992), others have assumed that organizational commitment is influenced by job satisfaction (Fresko, Kfir, & Nasser, 1997;Nguni, Sleegers, & Denessen, 2006;Reyes & Shin, 1995). The current study assumed the same direction of this relationship from job satisfaction to organizational commitment as the second group of researchers.…”
Section: Organizational Commitment and Ocbmentioning
confidence: 56%
“…However, the direction of Educational Psychology 479 this relationship is uncertain. While some researchers have claimed that organizational commitment influences job satisfaction (Culver, Wolfle, & Cross, 1990; Vandenberg & Lance, 1992), others have assumed that organizational commitment is influenced by job satisfaction (Fresko, Kfir, & Nasser, 1997;Nguni, Sleegers, & Denessen, 2006;Reyes & Shin, 1995). The current study assumed the same direction of this relationship from job satisfaction to organizational commitment as the second group of researchers.…”
Section: Organizational Commitment and Ocbmentioning
confidence: 56%
“…With regard to affective commitment, previous findings have shown that teacher commitment is positively related to job satisfaction (Culver, Wolfe, & Cross, 1990;Fresko, Kfir, & Nasser, 1997;Meyer, Allen, & Smith, 1993). Somech and Bogler (2002) showed that teacher commitment was positively related to organizational citizenship behavior, which is positively related to work-staff culture and job satisfaction.…”
Section: Current Researchmentioning
confidence: 92%
“…Finally, affective commitment, an important predictor of job satisfaction (Culver et al, 1990;Meyer et al, 1993), predicts beginning teachers' turnover intentions. This finding highlights how beginning teachers' lack of feeling that they belong to their schools generates their intentions to leave their schools or the profession at large.…”
Section: Supportedmentioning
confidence: 98%
“…Female teachers and those with greater teaching experience are reported to have higher job satisfaction levels than others. However, other researchers (e.g.. Culver, Wolfle, & Cross, 1990) have suggested that the effects of demographic attributes diminish when variables such as school climate are included in predictive models. In addition to these inconsistencies in the literature, the effects of demographic variables on teachers' sense of efficacy have been inadequately explored.…”
Section: Demographic Variablesmentioning
confidence: 98%